Artifacts with Feelings/Feeling Artifacts: Toward a Notion of Tacit Modalities to Support and Propel Anthropological Research. (3rd December 2021) - Rowsell, Jennifer; Abrams, Sandra Schamroth
Abstract : In this article, we consider the notion of tacit modalities as a theory and method for researchers. Based on research studies with individuals across ages and stages of life, we interviewed people about objects that they value, and what pervades all of the stories are tacit, lived properties that objects possess. The research ostensibly sought to extend work on the notion of artifactual literacies and tacit modalities, and, in the end, what stretched the research were sensory, embodied, and non‐representational experiences expressed by collaborators in the research. This article focuses on three people's stories about their felt experiences and sensory‐led (and laden) stories associated with objects. To analyze interview data, we apply transdisciplinary theories that offer the reader a syncretic conceptual experience of tacit modalities as a method within ethnographic work to locate sensorial, affective dimensions of objects.